Илья Ефимович Репин, 1844-1930 - Барагамян А. (Великие художники, 2010)
Экземпляры: ф.3 (20220225) / Инвентарный номер: 61869 / Цена: / Сис.шифр: 85.143(2Р=Рус)5 / Авт.знак: Р 41 / ГРНТИ: 18.31.31 / ББК: 85.143(2Р=Рус)5